Modelling learner discipline in a public school - Ramokgadi, Mabala William (My University, 2016)
The study explores the application of statistical methods to determine factors influencing learners to commit offences at school. Focus is on the time taken to commit a second offence and the number of repeat offences committed by learners after the first offence. The survival time from the first offence to a second offence is analysed by using Kaplan-Meier estimate of the survival function, the tests for equality of survivor functions, the Cox proportional hazards model, and the parametric hazards models. The number of repeat offences is analysed by fitting the Poisson regression model and Negative Binomial regression model. As many learners are expected not to offend again, the Zero Inflated Poisson (ZIP) model is also fitted to determine which factors influence learners not to commit a repeat offence. Factors that are related to the school environment were used in the study of learner offence. The categorical variables are learner grade (class), gender, home location, parental involvement, repeating a grade, suspected substance abuse, and hostel residence. The learner performance in the three selected subjects were used as continuous variables. The results of the analysis should also assist the schools in assessing the effectiveness of other forms of punishment since corporal punishment was abolished.
A research report submitted to the Faculty of Science, in partial fulfilment of the requirements for the degree of Master of Science, University of the Witwatersrand, Johannesburg, 2016.
Keywords: Statistics; Statistical methods; School discipline